Effect of drying delay on physiological quality of corn seeds - Silveira Borba, Cleverson; Andreoli, Claudinei; Vilela de Andrade, Ramiro; Tito de Azevedo, João; Carlos de Oliveira, Antonio (Pesquisa Agropecuaria Brasileira, 1998)
Corn seeds were harvested with 16% and 21% of moisture content and dryed for 0, 12, 24, 36, 48, 60, 72, 84, 96, 108, 120, 132, 144 and 156 hours after harvest to verify the effect of delaying desiccation on germination and vigor. The results pointed out that to obtain seed germination over 85%, seed drying may be retarded up to 84 hours when seeds were harvested with 21% of moisture content. The physiological quality of seeds decreased significantly when seed drying was retarded for more than 84 hours after harvesting seeds with high moisture content (21%). The physiological quality was not affected when seeds were harvested with low moisture content (16,0%) and desiccated up to 156 hours.
Keywords: germination; vigor; storage